The Septuagint and the Hexapla of 2 Samuel - Kauhanen, Tuukka (Journal of septuagint and cognate studies, 2024)
This article explores Hexaplaric readings in 2 Samuel in the context of the critical edition projects of the Göttingen LXX and the Hexapla Project. It highlights the interdependence of textual criticism of the LXX and Hexaplaric studies. Preliminary statistics reveal 446 readings attributed to Hexaplaric sources. Symmachus accounts for 45% of attributions, while Aquila follows with 35%. In the kaige section, however, readings attributed to Theodotion rise past Aquila into second place (30%) with a drastically different proportion of the attributed readings than in the non-kaige section (8%). A large number of the θ' readings in the kaige section may not derive from Theodotion after all. Notably, a good number of readings are attributed to two or more sources. The article also identifies thirteen marginal readings attributed to ο'. These readings often coincide with readings of the Hexaplaric recension of the LXX. These findings underscore the necessity for further investigation into the relationships between Hexaplaric sources and the textual transmission of the LXX. The forthcoming Göttingen LXX editions of the Books of Samuel pave way for a new Hexapla edition of Samuel. The Hexapla edition will present all the preserved Hexaplaric readings in the margins of the manuscripts, patristic sources, and the Hexaplaric recension with critical evaluations. The study ultimately contributes to the broader discourse on the transmission and reception of biblical texts in antiquity.